Computational Approaches in Supporting Special Education Domain: A Review - Mohemad, Rosmayati; Mamat, Nur Fadila Akma; Mohamad Noor, Noor Maizura; Che Alhadi, Arifah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Children with learning disabilities, emotional and behavioral problems are unable to accommodate with the standard educational programs. They are known as special children. Thus, special education is needed to support teaching and learning for this special children. In recent years, there has been an increase in the use of computational approaches to simplify various issues in special education. However, a comprehensive review that gives an overview about to what extent computational approaches are integrated and applied to support various issues in special education domain is still lacking. Thus, the objective of the paper is to explore to what extent the existing computational approaches are used in supporting the field of special education recently especially in categorizing children with learning disabilities and recommending an appropriate technique to increase their quality of life. Systematic Literature Review (SLR) is applied to perform this study. As a consequence, only studies from the year 2009 onwards have been searched. In summary, the main finding of this work shows that learning disabilities are the most recent topic that gets attention to research and there is a few research using an ontology to classify children with learning disability.